Assessment of Trends and Prospects for the Development of the Russian Economy in the Context of sanctions Pressure - M. A. Fedotova; T. V. Pogodina; S. V. Karpova (Финансы: теория и практика)
Improving the competitiveness of the national economy is one of the priorities of the socio-economic policy of the Russian Federation. In this regard, the identification of factors for increasing competitiveness is highly relevant for achieving the goals of sustainable development. In this paper, attention is paid to updating the problem posed and assessing the degree of influence of investment, technological, industrial, labor, social and financial factors on increasing Russia’s share in global GDP. The purpose of this study is to systematize the factors and identify promising areas for improving Russia’s competitiveness in the global economy. The object of the study is the development of the Russian Federation in 2014-2023 and for the future until 2026, and the subject is the study of factors and an assessment of their impact on improving the competitiveness of the national economy. Economic, mathematical and statistical methods were used as research methods. In particular, trend, correlation, regression, and comparative analysis have found practical application. As the main results of the study, it is necessary to highlight the justification of the influence of factors on increasing the competitiveness of the Russian economy; rank the influence of investment, technological, industrial, labor, social and financial factors on increasing Russia’s share in world GDP; determine the forecast values of Russia’s share in world GDPbased on the construction of the trend equation; identify the degree of influence of factors on the competitiveness of the national economy based on the calculation of correlation coefficients; and analyze the best practices of Russian raw materials companies in achieving world-class competitiveness.